Evaluating implementation of a hospital‐based cancer registry to improve childhood cancer care in low‐ and middle‐income countries - Melissa R. Maas; Allison Yang; Michele A. Muir; James B. Collins IV; Courtney Canter; Gevorg Tamamyan; Inam Chitsike; Francine Kouya; Kim Hoa Nguyen; Alia Ahmad; Ana Patricia Alcasabas; Yi‐Jin Gao; et al. (Cancer Medicine)
Abstract Purpose Cancer is a leading cause of global childhood mortality, affecting 400,000 children annually. While treatable with modern therapies, children living in low‐ and middle‐income countries (LMICs) have limited access to care and lower survival rates. Hospital‐based cancer registries (HBCRs) collect detailed patient information to critically evaluate and evolve care. The St. Jude Global Childhood Cancer Analytics Resource and Epidemiological Surveillance System (SJCARES) is a cloud‐based HBCR network facilitating quality data collection of pediatric cancer. Wide variation in the success of implementation has warranted further research into the implementation approach, to create a sustainable and adaptable HBCR in LMICs. Methods Seven of 89 sites using the SJCARES registry were selected, stratified by global region and stage of implementation. Semi‐structured interviews were conducted with key groups (clinicians, administrators, data clerks) using an interview guide developed from the Consolidation Framework for Implementation Research (CFIR). Interviews were conducted via a video‐telephone software program and transcribed by a transcription service. Transcripts were thematically coded using rapid qualitative analysis. Results A total of 18 participants (11 clinicians, 4 administrators, 3 data clerks) were interviewed. Several barrier themes were identified, including: difficulty integrating the registry into existing workflow; lack of resources; lack of government or administrative support; and damaged, misplaced, or illegible medical records. Facilitator themes were identified, including: internal support for the registry; clear and extensive training; and dedicated support staff. Conclusion Interviewed participants identified key barriers and facilitators to the implementation of the SJCARES registry across multiple phases. We plan to use these results to develop targeted implementation strategies including a readiness assessment tool to help guide more successful implementation of the SJCARES registry and other HBCRs in LMICs.